Actions for the overcoming of the teachers on the correct corporal posture in the children of the Primary Education - Julia Eva Pérez Arencibia; José Luís Suárez León; Angelo Hidalgo Martínez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
The correct corporal posture is an important aspect for the health and the quality of children's life since the early years and it is included as part of the hygiene thematic axis in the Health Principal Program which is developed in our schools. Taking into account the existence of the problematic situation in the Elementary Education, the authors of this investigation elaborated and validated an up-grading strategic for the primary teachers of the school "Isidoro Garcia" from Las Minas de Matahambres municipality, gaining outstanding results after applying the corresponding methods such as the observation, the survey and a Somatoscopical test. Besides, other samples of groups were included in the investigation, like the family, supervisors and principals.